Detecting special frames in sports videos - Yao, Wang. (2010)
Statistically, among the common video types, sports videos have more interesting moments than other types of videos. And it is often desired to automatically detect some special frames in sports videos, like close shot of athletes, illegality penalty, controversial goal, game result judgement, etc. In this thesis, we focus on two scenarios of video frame detection in sports videos: transition frame detection and video frame detection for sprint judgement.